Investigation of the effect of elbow pipes of Ti6Al4V, 304 stainless steel, AZ91 materials on erosion corrosion by finite element analysis - Gök, Kadir; Danışmaz, Merdin; Urtekin, Levent; Ada, Hediye Deniz; Gök, Arif (Acta Polytechnica, 2024)
Corrosion is the degradation of metals caused by chemical or electrochemical reactions with their environment. As a result of these reactions, undesirable conditions occur in the physical, chemical, mechanical and electrical properties of metals. These conditions cause parts made of metallic materials to become unusable. Erosion corrosion is one of the most common types of corrosion in fluid transfer. There are several methods for preventing erosion corrosion. First of all, some precautions should be taken to prevent wear. Intervention is very important in terms of cost, especially at the design stage. Measures such as wide angle bends, wall thickness of wear-resistant material and corrosion allowance can be taken, especially in applications where the flow direction needs to be changed. The aim of this study was to determine the effect of liquid fluid on erosion corrosion in Ti6Al4V, 304 stainless steel and MgAz91 elbow pipes by using the computer aided and finite element based AnsysWorkbench Explicit Dynamics module. For the design of the elbow pipe, SolidWorks was used for 3D studies. In the analysis of the pipe, the suitability of the pipe for the 3D model was examined. The effect of fluid rotation on the pipe walls and the effect of the pipe material on the flow along the pipe were determined. The standard k-e model based on the velocity-pressure relationship in continuous and steady flow was used for the flow calculations. The flow simulation showed that for all models the flow accumulation after rotation was more concentrated on the opposite walls of the pipe, as expected. The results obtained showed that the deformation in MgAZ91 material had the highest value at 9.14 × 10−8 mm. This situation has been interpreted to mean that it may vary depending on the flow rate automation. Designs on the old designs in the erosion structure of the liquid that occurs in the pipes with a new product design in the analysis design.